Engineering brown fat into skeletal muscle using ultrasound-targeted microbubble destruction gene delivery in obese Zucker rats: Proof of concept design - Bastarrachea, Raúl A.; Chen, Jiaxi; Kent, Jack W.; Nava González, Edna Judith; Rodríguez Ayala, Ernesto; Daadi, Marcel M.; Jorge, Barbara; Laviada Molina, Hugo A.; Comuzzie, Anthony G.; Chen, Shuyuan; Grayburn, Paul A. (2017)
plasmid cDNA contructs encoding a gene cocktail with BMP7/ PRDM16/PPARGC1A incorporated within microbubbles and intravenously delivered into their left thigh. Controls received UTMD with plasmids driving a DsRed reporter gene. An ultrasound transducer was directed to the thigh to disrupt the microbubbles within the microcirculation. Blood samples were drawn at baseline, and after treatment to measure glucose, insulin, and free fatty acids levels